2018
DOI: 10.25220/wnj.v01i2.0006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between carbohydrate, protein and fat intake with serum c-reactive protein level in lung cancer patients stage IIIB-IV

Abstract: Introduction:The aim of the study is to determine the correlation between carbohydrates, fat and protein intake with the serum C-Reactive-Protein level in lung cancer patients stage IIIB -IV. The progression of lung cancer is influenced by immune system, genetic factors and inflammatory response, therefore CRP can be relied as one of the parameters for predicting cancer cell growth. Methods: A cross sectional study was conducted in Dharmais Cancer Hospital Jakarta. Subjects were recruited by consecutive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…13 Previous research conducted by Anwar et al 13 in lung cancer patients in 2010 -2011 revealed similar results. Based on the research by Amanda et al 7 in lung cancer patients stage IIIB and IV in Dharmais Cancer Hospital in 2107, the average age of subjects was 55.83 ± 12.62 years with the majority in the range of 45-65 years, which is also similar to the findings of this research.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…13 Previous research conducted by Anwar et al 13 in lung cancer patients in 2010 -2011 revealed similar results. Based on the research by Amanda et al 7 in lung cancer patients stage IIIB and IV in Dharmais Cancer Hospital in 2107, the average age of subjects was 55.83 ± 12.62 years with the majority in the range of 45-65 years, which is also similar to the findings of this research.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research in 2017 at the Dharmais Cancer Hospital showed similar results: 36.7% and 22.5% subjects had normal and low BMI, respectively. 7 Total energy intake based on 24 hours food recall method showed median value of 1425.25 (425.9-2205.9) kcal with as much as 64.3% subjects had low energy intake. Disease and external factors can affect food intake and decreased appetite in cancer patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation